The Influence of Good Corporate Governance Mechanism, Profitability, and Liquidity on Sustainability Disclosure - Ramadoni, Lutfih; Bintara, Rista (Journal of Islamic Contemporary Accounting and Business, 2025)
This research aims to empirically test the influence of mechanisms Good Corporate Governance, profitability and liquidity on Sustainability Report disclosure. This research uses a quantitative approach with sampling used using a purposive sampling method, the analysis used in this research is multiple linear regression analysis managed via SPSS. The sample in this study consisted of 11 mining companies out of 75 mining companies reported to the IDX from 2019-2023. Corporate responsibilities that only prioritize economic interests must slowly begin to change. There are new concepts in sustainability, namely economics, environmental protection and social justice, all of which are expressed in Sustainability Reports. Therefore, this research aims to find things that can influence the disclosure of Sustainability Reports. The results of this research show that the independent board of commissioners has no influence on Sustainability Report disclosure, while the audit committee, profitability and liquidity influence Sustainability Report disclosure. For further research, it is hoped that other variables related to Sustainability Report disclosure can be added so that it can provide a broader picture.